2017
DOI: 10.1007/s10620-017-4626-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathological Risk Factors Associated with Liver Fibrosis and Steatosis in African-Americans with Chronic Hepatitis C

Abstract: Background & Aim Several factors involved in the development of liver fibrosis in African American patients with chronic hepatitis C (CHC) have not been well-studied. We aimed to evaluate some of these risk factors. Methods We reviewed pathology and medical records of 603 African Americans with chronic hepatitis C virus (HCV) infection at Howard University Hospital from Jan. 2004 to Dec. 2013. Among the clinical and pathological data collected were HIV (human immunodeficiency virus), HCV genotype, Hepatitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
0
7
0
1
Order By: Relevance
“…Studies have demonstrated that patients with CHC have a higher prevalence of hepatic steatosis and dyslipidemia than healthy individuals and patients with chronic hepatitis B [9,36]. Hepatic steatosis has been implicated in hepatocellular injury, including liver fibrosis [37] and necroinflammation, in patients with CHC [38]. Afsari et al revealed that patients with any degree of hepatic steatosis, as determined using the Brunt scale, had a 1.6 times higher odds ratio of advanced liver fibrosis or cirrhosis than those without hepatic steatosis [37].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that patients with CHC have a higher prevalence of hepatic steatosis and dyslipidemia than healthy individuals and patients with chronic hepatitis B [9,36]. Hepatic steatosis has been implicated in hepatocellular injury, including liver fibrosis [37] and necroinflammation, in patients with CHC [38]. Afsari et al revealed that patients with any degree of hepatic steatosis, as determined using the Brunt scale, had a 1.6 times higher odds ratio of advanced liver fibrosis or cirrhosis than those without hepatic steatosis [37].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted on HCV-infected individuals has demonstrated that hepatic steatosis and a history of diabetes mellitus contribute to the progression of liver fibrosis [13] . Factors such as sex [14] and hypertension [15] can also influence the progression of liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic hepatitis C virus (HCV) infection can lead to liver inflammation, fibrosis, and ultimately cirrhosis and hepatocellular carcinoma (HCC). The results of previous studies suggest that older age, HIV infection, obesity, and diabetes are associated with advanced stages of fibrosis in HCV . However, these risk factors are likely interdependent and potentially exacerbated by other conditions that may contribute to liver fibrosis .…”
Section: Introductionmentioning
confidence: 99%
“…
HIV infection, obesity, and diabetes are associated with advanced stages of fibrosis in HCV. [1][2][3][4][5] However, these risk factors are likely interdependent and potentially exacerbated by other conditions that may contribute to liver fibrosis. 6 Identifying patients with HCV who are at risk for advanced fibrosis is important for evidence-based, efficient HCC screening practices.
…”
mentioning
confidence: 99%